Answer:
Solve by factoring.
1. 2x^2+9x+26=-4x+5
2x²+9x+4x+26-5=0
2x²+13x+21=0
doing middle term factorization
2x²+7x+6x+21=0
x(2x+7)+3(2x+7)=0
(2x+7)(x+3)=0
either
x=-7/2
or
x=-3.
2.
3x^2-6x-4=0
comparing above equation with ax²+bx+c=0
we get
a=3
b=-6
c=-4
By using quadratic equation
x=
![\frac{ - b±\sqrt{ {b}^(2) - 4ac } }{2a}](https://img.qammunity.org/2022/formulas/mathematics/high-school/r671535i3x7qj5wcqe4yyjkx4mc6iquih1.png)
Substituting value
x=
![\frac{ 6±\sqrt{ {-6}^(2) - 4*3*-4 }}{2*-4}](https://img.qammunity.org/2022/formulas/mathematics/high-school/n1b3t2qg06unhajgnch5ui6qyywzcbn2wq.png)
x=
![\frac{ 6±\sqrt{ {84}}}{-8}](https://img.qammunity.org/2022/formulas/mathematics/high-school/vzdrwk5us6mw25cahssjeawpz45e49x7dt.png)
x=
![\frac{ 6±2\sqrt{ {21}}}{-8}](https://img.qammunity.org/2022/formulas/mathematics/high-school/5l0fytpib8m9h72pyhu3dgdy37bnrivka7.png)
-8x=6±2√21
taking positive
-8x=6+2√21
x=
![(6+2√21)/(-8)](https://img.qammunity.org/2022/formulas/mathematics/high-school/lwkny5ujaqcfl5mqlj7ujydedoixq3r2ul.png)
x=-
![(3+√21)/(4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/5jourjpt0i16ugwwj3wvf41u9ps09j4qh8.png)
taking negative
-8x=6-2√21
x=
![(6-2√21)/(-8)](https://img.qammunity.org/2022/formulas/mathematics/high-school/zxx87wlzjuho719wpzzplw199x8tkcwyw6.png)
x=-
![(3-√21)/(4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/dunkojtb47yfkq61zy6r1wmtuvm47q8pi5.png)